Method for synthesizing lithium iron phosphate by spodumene value-added metallurgy

By using spodumene value-added metallurgy to synthesize lithium iron phosphate in the spodumene lithium extraction process, iron phosphate is used as the nucleation seed crystal of lithium carbonate, the efficient and comprehensive utilization of lithium and iron elements is achieved, the problems of waste of resources and low economic benefits in the existing processes are solved, and the production efficiency and electrochemical performance are improved.

CN119683591APending Publication Date: 2025-03-25GUIZHOU XINREN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411829805.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The comprehensive utilization rate of valuable elements in the existing spodumene lithium extraction process is low, resulting in waste of resources and low economic benefits, and the inability to effectively utilize the iron elements contained in spodumene.

Method used

The method of synthesizing lithium iron phosphate by spodumene value-added metallurgy is adopted. By synthesizing iron phosphate and lithium carbonate in the same reactor, and using iron phosphate as the nucleation seed crystal of lithium carbonate, the precursor is able to synthesize LiFePO4/C in one step, saving production costs and improving efficiency.

Benefits of technology

It realizes efficient comprehensive utilization of lithium and iron elements, reduces energy consumption and acid consumption, improves the production efficiency and economic benefits of lithium iron phosphate positive electrode materials, and optimizes electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683591A_ABST
    Figure CN119683591A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing lithium iron phosphate by spodumene value-added metallurgy, which comprises the following steps: mixing spodumene and inorganic acid, then carrying out countercurrent leaching to obtain a leaching solution of valuable metals, carrying out two-stage impurity removal to remove impurity ions such as calcium, magnesium, aluminum, zinc and the like to obtain a purified solution, carrying out evaporation concentration, and then carrying out continuous synthesis to obtain lithium iron phosphate. The preparation method comprises the following steps: synthesizing an iron phosphate crystal nucleus for one time, continuing to synthesize lithium carbonate to obtain a precursor of lithium carbonate coated iron phosphate, and finally, adjusting the ratio of Li to Fe to P by proportioning to synthesize the LiFePO4 / C composite material in one step. According to the process for one-step synthesis of the LiFePO4 / C composite material and the byproduct sodium sulfate by extracting lithium and iron elements from spodumene, resource utilization of valuable metals is completed, lithium carbonate and iron phosphate are uniformly compounded, the performance of the precursor is reliable, and finally, the LiFePO4 / C composite material is synthesized in a short process. The method is short in process, low in acid consumption, low in energy consumption, simple in equipment, easy to operate and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrometallurgical preparation of lithium-ion battery positive electrode materials, and in particular to a method for synthesizing lithium iron phosphate by spodumene value-added metallurgy. Background Art

[0002] The current lithium extraction process of spodumene is mainly based on the sulfuric acid method. However, in the typical process, every ton of lithium carbonate produced will produce about 10 tons or even more insoluble lithium smelting slag. Most of the existing methods use lithium smelting slag for primary utilization in the field of building materials by doping. The process is simple, but the product added value is low and the economic benefits are limited; or although the elements are separated, the products are all intermediate products, the utilization rate is low, and the use of acid and alkali solutions cannot be avoided, the cost is high, and the overall economic benefits are low. Therefore, in order to make full use of the elements in the slag and increase economic benefits, it is hoped to invent a new process for comprehensive recovery of lithium and iron elements in raw materials. High-value comprehensive recovery and utilization of valuable elements in spodumene and reduction of waste will provide a new way to alleviate environmental pressure and solve the bottleneck that restricts the development of the new energy industry chain.

[0003] In the prior art, the patent number CN114606383 A discloses a method for comprehensive recovery of valuable elements in industrial leaching slag of spodumene, which obtains ferrosilicon and alumina by washing, evaporation, filtration, mixing, roasting, and magnetic separation. The method only stops at the initial separation and generates intermediate products for the recovery of iron, and fails to achieve effective utilization. The patent number CN 118792502 A discloses a method for efficient lithium extraction from spodumene acid clinker and preparation of low-iron and low-sulfur silicon-aluminum micropowder, and obtains low-iron and low-sulfur silicon-aluminum micropowder by pulping, grading, grinding, flotation, concentration, solid-liquid separation and other treatments of the leaching slag. The method still does not effectively utilize the iron element. In addition, from the currently reported patents or papers and other materials, they all focus on the comprehensive utilization of lithium slag produced by the existing spodumene lithium extraction process for resource utilization, and most of them separate the iron element from the system, and there is no comprehensive utilization means of lithium and iron elements for spodumene with higher iron content. At the same time, in the current market situation where there is a serious oversupply of lithium iron phosphate, it is particularly important to optimize and upgrade the lithium iron phosphate production process, reduce costs and enhance product competitiveness.

[0004] In view of this, it is necessary to develop a method for synthesizing lithium iron phosphate through spodumene value-added metallurgy, while utilizing the lithium and iron elements in the mineral to solve the problem of low comprehensive utilization rate of valuable elements in existing spodumene lithium extraction technology. Summary of the invention

[0005] In view of the above-mentioned shortcomings that currently exist, the present invention provides a method for synthesizing lithium iron phosphate through spodumene value-added metallurgy. In the present invention, iron phosphate and lithium carbonate are processed in the same reactor to synthesize iron phosphate and lithium carbonate successively. The iron phosphate synthesized first is used as a nucleation seed for lithium carbonate, which can not only synthesize a uniformly coated precursor, but also solve the problem of difficult filtration in the production process of iron phosphate. The present invention adopts a precursor to synthesize LiFePO4 / C in one step, which can save the production costs of the drying process, crushing process, packaging process and transportation process of iron phosphate and lithium carbonate respectively, improve production efficiency, and provide a new method for the synthesis of lithium iron phosphate positive electrode materials.

[0006] In order to achieve the above object, the present invention provides a method for synthesizing lithium iron phosphate by spodumene value-added metallurgy, comprising the following steps:

[0007] S1, after drying and mechanical activation of spodumene, adding an inorganic acid solution for countercurrent leaching, and then washing and separating to obtain a leachate containing valuable elements;

[0008] S2, adding a reducing agent to the leaching solution and mixing, and adding a pH adjusting agent to adjust the pH value to 3.5-5.5 at 25-90° C., adding a purifying agent to react after aging to obtain a purified solution;

[0009] S3, after the purified liquid is pre-concentrated by evaporation, an oxidant and a phosphorus source are added and mixed, an oxidation reaction is carried out at 25 to 90° C., and then a pH adjusting agent is slowly added, and the pH value is adjusted to 1 to 3 at 55 to 95° C. to carry out a primary synthesis reaction;

[0010] S4, adding sodium carbonate solution to the solution obtained by the primary synthesis reaction, continuing the secondary synthesis reaction at 55-95° C. to obtain a residual mother liquor and a precursor of lithium carbonate-coated iron phosphate; wherein the residual mother liquor is decarbonized and concentrated by sulfuric acid and recycled; at 55-95° C., the precursor of lithium carbonate-coated iron phosphate is washed and separated to obtain a washed precursor;

[0011] S5. Evenly mix the washed precursor with an iron source, a lithium source, a phosphorus source, and a carbon source, and then grind, dry, sinter, and crush in sequence to obtain LiFePO4 / C.

[0012] According to one aspect of the present invention, in step S1,

[0013] The 200 mesh screening rate of the mechanically activated spodumene is greater than 80%;

[0014] The inorganic acid solution is at least one of sulfuric acid, nitric acid, hydrochloric acid, and perchloric acid; H +The concentration is 10-28 mol / L; the mass-volume concentration ratio of the spodumene to the inorganic acid solution is (1:2-6);

[0015] The countercurrent leaching temperature is 60-110° C., and the countercurrent leaching time is 3-15 hours.

[0016] According to one aspect of the present invention, in step S2,

[0017] The reducing agent includes at least one of Zn, Fe, Cu, ZnSO3, Fe2(SO3)3, and CuSO3; preferably, the reducing agent is Fe; the amount of the reducing agent added is the amount of Fe in the leaching solution. 3+ Converted to Fe 2+ The amount of the purifier is 1 to 1.5 times the theoretical amount of the reducing agent required; the purifier includes trisodium phosphate; the amount of the purifier added is Ca in the solution 2+ Mg 2+ 1 to 1.5 times the theoretical amount of the scavenger required for the reaction;

[0018] The aging time is 1 to 3 hours; the temperature for adding the purifier to react is 25 to 90° C. and the time is 1 to 5 hours.

[0019] According to one aspect of the present invention, the pH adjuster includes at least one of NaOH, NH4OH, and Na2CO3.

[0020] According to one aspect of the present invention, the Al in the purification solution 3+ , Cu 2+ Mg 2+ 、Zn 2+ , Ca 2+ The content is ≤10ppm.

[0021] According to one aspect of the present invention, in step S3,

[0022] The oxidant is at least one of hydrogen peroxide, sodium chlorate, sodium hypochlorite, sodium persulfate, ammonium persulfate or potassium persulfate; the amount of the oxidant added is the amount of Fe in the purified liquid after evaporation pre-concentration. 2+ Converted to Fe 3+ 1.2 to 1.5 times the theoretical amount of the required oxidant; preferably, the oxidant is hydrogen peroxide;

[0023] The phosphorus source is at least one of hydrogen peroxide, sodium chlorate, sodium hypochlorite, sodium persulfate, ammonium persulfate or potassium persulfate; the molar ratio of Fe element to P element in the mixed solution obtained by adding the oxidant and the phosphorus source and mixing them is 1:(1.1-1.3);

[0024] The time of the primary synthesis reaction is 3 to 10 hours.

[0025] According to one aspect of the present invention, in step S4,

[0026] The concentration of the sodium carbonate solution is 200-280 g / L;

[0027] The secondary synthesis reaction time is 3 to 10 hours;

[0028] The CO3 in the precipitated mother liquor 2+ The concentration is 15-25g / L.

[0029] According to one aspect of the present invention, in step S5,

[0030] The iron source is at least one of ferric phosphate, ferrous sulfate, ferrous oxalate, ferrous acetate, and nano-ferric oxide;

[0031] The lithium source is at least one of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium acetate; the phosphorus source is at least one of iron phosphate, phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium phosphate;

[0032] The carbon source is at least one of glucose, sucrose, white sugar, citric acid, starch, and polyethylene glycol;

[0033] The molar ratio of Li:Fe:P in the mixed material obtained by the uniform mixing is (1-1.1):(0.95-0.99):1;

[0034] The mass of the carbon source is 3-9 wt. % of the mass of the mixed material.

[0035] According to one aspect of the present invention, in step S5, the impurity content in the washed precursor satisfies: Na+K<250ppm, Ca<50ppm, Mg<30ppm, Al<10ppm, and magnetic impurities<0.5ppm.

[0036] Based on the same inventive concept, the present invention also provides a carbon-coated lithium iron phosphate positive electrode material, and the carbon-coated lithium iron phosphate positive electrode material is prepared by any of the methods described above.

[0037] Beneficial effects of the present invention:

[0038] (1) The present invention reduces the traditional high-temperature sintering process for the treatment of spodumene and fully reduces energy consumption. The two-stage countercurrent leaching is used to "dry up" the valuable metals in the spodumene concentrate while significantly reducing acid consumption. The extraction rates of lithium, iron and sodium can reach 90%, 94% and 95% respectively, realizing efficient and comprehensive utilization of valuable resources;

[0039] (2) The precursor of the present invention adopts a continuous synthesis process, and the synthesis of lithium carbonate is continued after the iron phosphate nucleus is synthesized once in the same reactor. The iron phosphate synthesized first is used as a nucleation seed for lithium carbonate, which is beneficial to the synthesis of lithium carbonate, can make the lithium carbonate evenly coated on the surface of the iron phosphate, and can also solve the problem of difficult filtration in the production process of iron phosphate;

[0040] (3) The present invention synthesizes the LiFePO4 / C composite material in one step through the precursor, thereby saving the production costs of the drying process, crushing process, packaging process, and transportation process of iron phosphate and lithium carbonate, and improving production efficiency;

[0041] (4) The present invention adopts a small amount of Fe-deficient ratio, and its regenerated lithium iron phosphate positive electrode material will produce Fe vacancies. This is conducive to reducing Li + The diffusion barrier of Li + The transmission rate in one-dimensional channels, thereby improving the rate performance of the material;

[0042] (5) The present invention adopts a carbon thermal reduction method to prepare a carbon-coated lithium iron phosphate positive electrode material through two-stage calcination, and controls the slow release of water vapor generated during the first stage of calcination, which helps to refine the grains and reduce particle agglomeration. The obtained lithium iron phosphate positive electrode material has good particle uniformity and excellent electrochemical performance;

[0043] (6) The present invention uses lithium carbonate to coat the precursor of iron phosphate to synthesize lithium iron phosphate, which can save part of the process of traditional synthesis of lithium iron phosphate, thereby greatly reducing the process cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A schematic flow diagram of a method for synthesizing lithium iron phosphate by spodumene value-added metallurgy of the present invention;

[0045] Figure 2 This is a SEM image of the carbon-coated lithium iron phosphate positive electrode material 1 prepared in Example 1 of the present invention;

[0046] Figure 3 This is the XRD pattern of the carbon-coated lithium iron phosphate positive electrode material 1 prepared in Example 1 of the present invention;

[0047] Figure 4 This is a charge and discharge curve diagram of a button-type battery assembled with the carbon-coated lithium iron phosphate positive electrode material 1 prepared in Example 1 of the present invention;

[0048] Figure 5 This is a charge and discharge curve diagram of a button-type battery assembled with the carbon-coated lithium iron phosphate positive electrode material 2 prepared in Example 2 of the present invention;

[0049] Figure 6This is a charge and discharge curve diagram of a button-type battery assembled with the carbon-coated lithium iron phosphate positive electrode material 3 prepared in Example 3 of the present invention;

[0050] Figure 7 This is a charge and discharge curve diagram of a button-type battery assembled with the carbon-coated lithium iron phosphate positive electrode material 4 prepared in Comparative Example 1 of the present invention;

[0051] Figure 8 This is a charge and discharge curve diagram of a button-type battery assembled with the carbon-coated lithium iron phosphate positive electrode material 5 prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0052] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.

[0053] Example 1

[0054] A method for synthesizing lithium iron phosphate by spodumene value-added metallurgy, the process flow chart of which is as follows Figure 1 As shown, the following steps are included:

[0055] (1) After drying and mechanical activation, spodumene concentrate with a 200-mesh screening rate greater than 85% is obtained. + The sulfuric acid solution with a concentration of 16 mol / L was mixed at a ratio of 1:4 (g / mL), countercurrent leached at 95°C for 10 h, and the leaching solution was obtained by washing and separation;

[0056] (2) The leaching solution and iron powder (reducing agent) are mixed according to the "Fe 3+ →Fe 2+ ” Mix with 1.2 times the conversion amount, adjust the pH value to 5.1 with Na2CO3 at 60℃, and add Ca 2+ Mg 2+ 、Zn 2+ 1.3 times the amount of trisodium phosphate required for the reaction was reacted at 65°C for 2.5h to obtain a purified solution;

[0057] (3) After the purified liquid is evaporated and pre-concentrated, it is mixed with hydrogen peroxide (oxidant) according to the "Fe" in the purified liquid after evaporation and pre-concentration. 2+ →Fe3+ "Mixed with 1.4 times the amount required for conversion; mixed with phosphoric acid at a molar ratio of Fe:P in the mixed solution of 1:1.2; oxidized at 50°C for 3h to obtain an oxidized solution. Then, NaOH was slowly added, and the pH was adjusted to 2.1 at 80°C for a synthesis reaction;

[0058] (4) Add 250 g / L sodium carbonate solution to the solution obtained from the first synthesis reaction, and continue the second synthesis reaction at 85°C to obtain a residual mother liquor and a precursor of lithium carbonate-coated iron phosphate. 2+ The concentration is 18g / L. The precursor is washed and separated at 75°C to obtain a washed precursor. Its impurity content is: Na+K is 98ppm, Ca is 15ppm, Mg is 3ppm, Al is 1ppm, and magnetic impurities are 0.1ppm. The remaining mother liquor is decarbonized by sulfuric acid, concentrated and recycled;

[0059] (5) The washed precursor is mixed with iron phosphate, lithium carbonate and glucose at a molar ratio of Li:Fe:P of 1.02:0.97:1 (the mass of glucose is 3-9wt.% of the mass of the mixture), and then ground, dried, sintered and crushed to obtain LiFePO4 / C composite positive electrode material 1. Material 1 is assembled into a button cell and the electrochemical performance is tested. The test results are as follows: Figure 4 As shown in the figure, the charge and discharge curve of the regenerated positive electrode material under the conditions of 3.75-2.0V, 0.1C, and 25°. It can be seen that the 0.1C first discharge capacity of the regenerated lithium iron phosphate positive electrode material is 161.73mAh / g, and the 0.1C first coulomb efficiency is 98.24%.

[0060] The obtained carbon-coated lithium iron phosphate positive electrode material was scanned by electron microscope. Figure 2 As shown, the SEM image shows that the material has a regular morphology, good uniformity in the distribution of large and small particles, and good carbon coating on the surface of the material.

[0061] The regenerated lithium iron phosphate positive electrode material 1 is subjected to XRD detection, such as Figure 3 As shown, compared with the jade standard card PDF-#83-2092, the diffraction peaks are consistent with the marked card. The results show that there is no impurity phase and it is a single olivine-type lithium iron phosphate.

[0062] Example 2

[0063] A method for synthesizing lithium iron phosphate by spodumene value-added metallurgy comprises the following steps:

[0064] (1) After drying and mechanical activation, spodumene concentrate with a 200-mesh screening rate greater than 90% is obtained. +The sulfuric acid solution with a concentration of 20 mol / L was mixed at a ratio of 1:4 (g / mL), countercurrent leached at 85°C for 12 h, and the leachate was washed and separated to obtain a leachate;

[0065] (2) The leaching solution and iron powder (reducing agent) are mixed according to the "Fe 3+ →Fe 2+ ” Mix 1.25 times the conversion amount, adjust the pH to 5.0 with Na2CO3 at 65℃, age for 2h, and then add Ca 2+ Mg 2+ 、Zn 2+ 1.35 times the amount of trisodium phosphate required for the reaction was reacted at 70°C for 3 hours to obtain a purified solution;

[0066] (3) After the purified liquid is evaporated and pre-concentrated, it is mixed with hydrogen peroxide (oxidant) to remove the "Fe 2+ →Fe 3+ "Mix with 1.4 times the amount required for conversion; mix with phosphoric acid at a molar ratio of Fe:P in the solution of 1:1.15; oxidize at 50°C for 3h to obtain an oxidized solution. Then slowly add NaOH, adjust the pH to 2.2 at 80°C to carry out a synthesis reaction;

[0067] (4) Add 230 g / L sodium carbonate solution to the solution obtained from the first synthesis reaction, and continue the second synthesis reaction at 85°C to obtain a residual mother liquor and a precursor of lithium carbonate-coated iron phosphate. 2+ The concentration is 20g / L. The precursor is washed and separated at 85°C to obtain a washed precursor. Its impurity content is: Na+K is 106ppm, Ca is 21ppm, Mg is 5ppm, Al is 3ppm, and magnetic impurities are 0.2ppm. The remaining mother liquor is decarbonized by sulfuric acid, concentrated and recycled;

[0068] (5) The washed precursor was mixed with iron phosphate, lithium carbonate and glucose at a molar ratio of Li:Fe:P of 1.03:0.97:1 (the mass of glucose was 3-9wt.% of the mass of the mixture), and then ground, dried, sintered and crushed to obtain LiFePO4 / C composite positive electrode material 2. Material 2 was assembled into a button cell and the electrochemical performance was tested. The test results are as follows: Figure 5 As shown in the figure, the charge and discharge curve of the regenerated positive electrode material under the conditions of 3.75-2.0V, 0.1C, and 25°. It can be seen that the 0.1C first discharge capacity of the regenerated lithium iron phosphate positive electrode material is 161.59mAh / g, and the 0.1C first coulomb efficiency is 98.28%.

[0069] Example 3

[0070] A method for synthesizing lithium iron phosphate by spodumene value-added metallurgy comprises the following steps:

[0071] (1) After drying and mechanical activation, spodumene concentrate with a 200-mesh sieving rate greater than 95% is obtained. + The sulfuric acid solution with a concentration of 10 mol / L was mixed at a ratio of 1:6 (g / mL), countercurrent leached at 105°C for 15 h, and the leaching solution was obtained by washing and separation;

[0072] (2) The leaching solution and iron powder (reducing agent) are mixed according to the "Fe 3+ →Fe 2+ ” Mix 1.3 times the conversion amount, adjust the pH to 5.2 with Na2CO3 at 65℃, age for 2h, and add Ca 2+ Mg 2+ 、Zn 2+ 1.4 times the amount of trisodium phosphate required for the reaction was reacted at 70°C for 3h to obtain a purified solution;

[0073] (3) After the purified liquid is evaporated and pre-concentrated, it is mixed with hydrogen peroxide (oxidant) according to the "Fe 2+ →Fe 3+ "Mix with 1.4 times the amount required for conversion; mix with phosphoric acid at a molar ratio of Fe:P in the solution of 1:1.25; oxidize at 50°C for 3h to obtain an oxidized solution. Then slowly add NaOH, adjust the pH to 2.3 at 80°C to carry out a synthesis reaction;

[0074] (4) Add 275 g / L sodium carbonate solution to the solution obtained from the first synthesis reaction, and continue the second synthesis reaction at 85°C to obtain a residual mother liquor and a precursor of lithium carbonate-coated iron phosphate. 2+ The concentration is 23g / L. The precursor is washed and separated at 85°C to obtain a washed precursor. Its impurity content is: Na+K is 72ppm, Ca is 9ppm, Mg is 1ppm, Al is 2ppm, and magnetic impurities are 0.1ppm. The remaining mother liquor is decarbonized by sulfuric acid, concentrated and recycled;

[0075] (5) The washed precursor is mixed with iron phosphate, lithium carbonate and glucose at a molar ratio of Li:Fe:P of 1.02:0.98:1 (the mass of glucose is 3-9wt.% of the mass of the mixture), and then ground, dried, sintered and crushed to obtain LiFePO4 / C composite positive electrode material 3. Material 3 is assembled into a button cell and the electrochemical performance is tested. The test results are as follows Figure 6As shown in the figure, the charge and discharge curve of the regenerated positive electrode material under the conditions of 3.75-2.0V, 0.1C, and 25°. It can be seen that the 0.1C first discharge capacity of the regenerated lithium iron phosphate positive electrode material is 161.57mAh / g, and the 0.1C first coulomb efficiency is 98.57%.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that the leaching time in the material in step (1) is 2 h, and the other conditions are completely the same. The obtained regenerated lithium iron phosphate positive electrode material 4 is assembled into a button cell and the electrochemical performance test is performed. The test results are as follows: Figure 7 As shown, the figure shows the charge and discharge curve of the regenerated positive electrode material under the conditions of 3.75-2.0V, 0.1C, and 25°. It can be seen that the 0.1C first discharge capacity of the regenerated lithium iron phosphate positive electrode material is 161.42mAh / g, and the 0.1C first coulomb efficiency is 98.56%. The extraction rate of lithium in the leaching solution is significantly reduced. This is because the leaching reaction time is not sufficient. The ore sample components and component leaching conditions used in each embodiment and comparative example are shown in Table 1.

[0078] Table 1:

[0079]

[0080]

[0081] Comparative Example 2

[0082] The difference from Example 2 is that the molar ratio of Li:Fe:P in the material of step (5) is 1:1:1, and the other conditions are completely the same, and the obtained regenerated lithium iron phosphate positive electrode material 5. Material 5 is assembled into a button cell and the electrochemical performance test is carried out. The test results are as follows Figure 8 As shown in the figure, the charge and discharge curve of the regenerated positive electrode material under the conditions of 3.75-2.0V, 0.1C, and 25°. It can be seen that the 0.1C first discharge capacity of the regenerated lithium iron phosphate positive electrode material is 157.54mAh / g, and the 0.1C first coulomb efficiency is 96.57%. The capacity has a significant downward trend compared with Example 2. The possible reason is that the increase in the Fe site ratio reduces the diffusion coefficient of lithium ions inside the material. During the charge and discharge process of the battery, the diffusion of lithium ions is hindered to a certain extent, and the capacity cannot be exerted.

[0083] The electrochemical properties of the lithium iron phosphate positive electrode materials obtained in the examples and comparative examples are shown in Table 2.

[0084] Table 2:

[0085]

[0086] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for synthesizing lithium iron phosphate by spodumene value-added metallurgy, characterized in that: The following steps are involved: S1, after drying and mechanical activation of spodumene, adding an inorganic acid solution for countercurrent leaching, and then washing and separating to obtain a leachate containing valuable elements; S2, adding a reducing agent to the leaching solution and mixing, and adding a pH adjusting agent to adjust the pH value to 3.5-5.5 at 25-90° C., adding a purifying agent to react after aging to obtain a purified solution; S3, after the purified liquid is pre-concentrated by evaporation, an oxidant and a phosphorus source are added and mixed, an oxidation reaction is carried out at 25 to 90° C., and then a pH adjusting agent is slowly added, and the pH value is adjusted to 1 to 3 at 55 to 95° C. to carry out a primary synthesis reaction; S4, adding sodium carbonate solution to the solution obtained by the primary synthesis reaction, continuing the secondary synthesis reaction at 55-95° C. to obtain a residual mother liquor and a precursor of lithium carbonate-coated iron phosphate; wherein the residual mother liquor is decarbonized and concentrated by sulfuric acid and recycled; at 55-95° C., the precursor of lithium carbonate-coated iron phosphate is washed and separated to obtain a washed precursor; S5. Evenly mix the washed precursor with an iron source, a lithium source, a phosphorus source, and a carbon source, and then grind, dry, sinter, and crush in sequence to obtain LiFePO4 / C.

2. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S1, The 200 mesh screening rate of the mechanically activated spodumene is greater than 80%; The inorganic acid solution is at least one of sulfuric acid, nitric acid, hydrochloric acid, and perchloric acid; H + The concentration is 10-28 mol / L; the mass-volume concentration ratio of the spodumene to the inorganic acid solution is (1:2-6); The countercurrent leaching temperature is 60-110° C., and the countercurrent leaching time is 3-15 hours.

3. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S2, The reducing agent includes at least one of Zn, Fe, Cu, ZnSO3, Fe2(SO3)3, and CuSO3; the amount of the reducing agent added is the amount of Fe in the leaching solution. 3+ Converted to Fe 2+ The amount of the purifier is 1 to 1.5 times the theoretical amount of the reducing agent required; the purifier includes trisodium phosphate; the amount of the purifier added is Ca in the solution 2+ Mg 2+ 1 to 1.5 times the theoretical amount of the scavenger required for the reaction; The aging time is 1 to 3 hours; the temperature for adding the purifier to react is 25 to 90° C. and the time is 1 to 5 hours.

4. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: The pH adjuster includes at least one of NaOH, NH4OH, and Na2CO3.

5. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: The Al in the purification solution 3+ , Cu 2+ Mg 2+ 、Zn 2+ , Ca 2+ The content is ≤10ppm.

6. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S3, The oxidant is at least one of hydrogen peroxide, sodium chlorate, sodium hypochlorite, sodium persulfate, ammonium persulfate or potassium persulfate; the amount of the oxidant added is the amount of Fe in the purified liquid after evaporation pre-concentration. 2+ Converted to Fe 3+ 1.2 to 1.5 times the theoretical amount of the oxidant required; The phosphorus source is at least one of hydrogen peroxide, sodium chlorate, sodium hypochlorite, sodium persulfate, ammonium persulfate or potassium persulfate; the molar ratio of Fe element to P element in the mixed solution obtained by adding the oxidant and the phosphorus source and mixing them is 1:(1.1-1.3); The time of the primary synthesis reaction is 3 to 10 hours.

7. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S4, The concentration of the sodium carbonate solution is 200-280 g / L; The secondary synthesis reaction time is 3 to 10 hours; The CO3 in the precipitated mother liquor 2+ The concentration is 15-25g / L.

8. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S5, The iron source is at least one of ferric phosphate, ferrous sulfate, ferrous oxalate, ferrous acetate, and nano-ferric oxide; The lithium source is at least one of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium acetate; the phosphorus source is at least one of iron phosphate, phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium phosphate; The carbon source is at least one of glucose, sucrose, white sugar, citric acid, starch, and polyethylene glycol; The molar ratio of Li:Fe:P in the mixed material obtained by the uniform mixing is (1-1.1):(0.95-0.99):1; The mass of the carbon source is 3-9 wt. % of the mass of the mixed material.

9. The method for synthesizing lithium iron phosphate by spodumene value-added metallurgy according to claim 1, characterized in that: In step S5, the impurity content in the washed precursor satisfies the following conditions: Na+K<250ppm, Ca<50ppm, Mg<30ppm, Al<10ppm, and magnetic impurities<0.5ppm.

10. A carbon-coated lithium iron phosphate positive electrode material, characterized in that: The carbon-coated lithium iron phosphate positive electrode material is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for comprehensively recovering valuable elements in spodumene industrial leaching residues

    CN114606383A

  • Method for efficiently extracting lithium from spodumene acid clinker and preparing low-iron low-sulfur silicon-aluminum micropowder

    CN118792502A